2013
DOI: 10.1007/s00246-013-0826-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of SMAD5 is Associated With Kawasaki Disease

Abstract: Mothers against decapentaplegic homolog (SMAD) proteins are intracellular mediators of members of the transforming growth factor-β (TGF-β) superfamily, which are activated by bone morphogenetic proteins (BMPs). On activation, SMAD5 forms heterometric SMAD complexes, which are translated to the nucleus where they regulate gene transcription. TGF-β induces T cell activation and cardiovascular disease, two important features of Kawasaki disease (KD), whereas BMP is associated with coronary artery disease. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Another report from our group revealed that 1 SNP (rs3206634; T>C) of SMAD5 was associated with susceptibility to KD, but not associated with patients with CAL in a recessive model. This suggests that the minor allele C may increase the risk of development of KD approximately 2.3 folds, compared with the control group in the Korean population 23) .…”
Section: Tgf-β Signaling Pathwaymentioning
confidence: 90%
“…Another report from our group revealed that 1 SNP (rs3206634; T>C) of SMAD5 was associated with susceptibility to KD, but not associated with patients with CAL in a recessive model. This suggests that the minor allele C may increase the risk of development of KD approximately 2.3 folds, compared with the control group in the Korean population 23) .…”
Section: Tgf-β Signaling Pathwaymentioning
confidence: 90%
“…set 2)276/282xOnouchi et al [92] (Indep. set 3)267/752xOnouchi et al [95]546/947Yes ( ITPKC )Yes ( ITPKC ) i Yes ( ITPKC ) i ChinesePeng et al [97]223/318Yes ( ITPKC )Yes (ITPKC)NoKhor et al [61]130/568Yes ( ITPKC )xxTaiwaneseChi et al [18]385 (of which 158 trios)/1158NoNoxLin et al [73]280/492Yes ( ITPKC )NoxKuo et al [71]341/1190Yes ( ITPKC )Yes ( ITPKC ) j NoAbove-mentioned studies combined999/2781Yes ( ITPKC )xxKuo et al [68]381/569No k Yes ( ITPKC )xKhor et al [61]438/446Yes ( ITPKC )xxEuropeanKhor et al [61] (GWAS)405/6252 (10)Yes ( ITPKC )xxKhor et al [61] (Replication) 605 trios, 139 siblings l xxUSOnouchi et al [92]209 triosYes ( ITPKC )Yes ( ITPKC )Yes ( ITPKC )TGF-β pathwayJapaneseCho et al [20]105/303Yes ( SMAD5 )NoxHan ChinesePeng et al [98]392/421Yes ( TGFB2 , SMAD3 , ADAM17 )Yes ( TGFB2 )NoTaiwaneseKuo et al [70]381/569Yes ( SMAD3 )NoNoKoreanChoi et al [21]105/500Yes ( TGFBR2 )Yes ( TGFBR2 )xEuropean descent…”
Section: Geneticsmentioning
confidence: 99%
“…This tool can better explore the association between diseases and gene function when combined with the analysis of biological mechanisms (Gong et al, ; Zou et al., ). Previous studies discovered that various genetic variations played potential roles in the occurrence and progression of KD, such as the genetic polymorphisms of B‐cell lymphoid kinase ( BLK ), human leukocyte antigen ( HLA ), CD40 , inositol 1,4,5‐trisphosphate 3‐kinase C ( ITPKC ), caspase‐3 ( CASP3 ), mothers against decapentaplegic homolog ( SMAD ), and cytotoxic T lymphocyte associated antigen‐4 ( CTLA‐4 ) (Cho, Han, Cha, Jung, & Yoon, ; Kuo et al., ; Lou et al., ; Onouchi et al., ; Onouchi et al., ; Yan et al., ). Multifarious GWAS analysis and genomic function studies have also uncovered relationships among SNPs in platelet endothelial aggregation receptor 1 ( PEAR1 ) loci and cardiovascular diseases primarily involved in endothelial (e.g., endothelial migration and angiogenesis) and platelet functions (Backman et al., ; Faraday et al., ; Fisch et al., ; Lewis et al., ; Vandenbriele et al., ).…”
Section: Introductionmentioning
confidence: 99%